Exploring the role of meaning in non-Māori speakers’ ‘proto-lexicon’ - Wakayo Mattingley; Forrest Panther; Simon Todd; Jennifer Hay; Jeanette King; Peter J. Keegan (PLoS ONE, 2026)
Previous work has demonstrated that New Zealanders who do not speak Māori but are regularly exposed to the language develop implicit knowledge of it. The core of this knowledge, it has been argued, is the ‘proto-lexicon’—a set of stored word-forms, without associated meaning, which yields subsequent Māori phonotactic and morphological knowledge. Previous research shows that having a proto-lexicon gives learners a head start in learning Māori word meanings in formal education. We investigate experimentally whether the proto-lexicon confers an advantage for attaching meanings to words. In Experiment 1, non-Māori-speaking New Zealanders were tested on their ability to identify meanings of Māori words in a forced-choice definition task, and they did this relatively well. Then, words with low accuracy were selected for Experiment 2, where non-Māori-speaking New Zealanders and non-New Zealanders were asked to learn meanings for Māori words and nonwords. New Zealanders performed better, indicating that familiarity with Māori word shapes confers an advantage. However, they showed no greater advantage for real words over nonwords. If these words are definitely in the proto-lexicon, then this would suggest that knowledge of individual word-forms does not, in fact, confer an advantage. In Experiment 3, we therefore explore whether the words in Experiment 2 are actually robustly in the participants’ proto-lexicon, by running a word identification task with the same participants. These words were not robustly distinguished from nonwords. By selecting words for their lack of semantic knowledge, we also inadvertently selected words that do not appear to be in the proto-lexicon. Together, our results indicate that different levels of semantic knowledge exist for different words, even when we consider only words that cannot confidently be said to be in a full lexicon. The results suggest that the claim of previous studies that the proto-lexicon is ‘without semantics’ may be oversimplified.